Effect of Macroeconomic Variables on Third-Party Funds in Islamic Commercial Banks in Indonesia - Ryan Rahmah Maulayati; Muthi Adillah Bahril; Sri Herianingrum (Department of Islamic Economics, Islamic University of Indonesia, 2020)
The purpose of this article is to look at the long-term and short-term relationships between macroeconomic variables, namely the exchange rate, inflation and IPI to third party funds with Islamic commercial banks in Indonesia. This article uses quantitative research methods, the data used is secondary data with the time series type from January 2014-December 2018, the analytical tool used is VECM, which is a form of VAR detected. Before the final results are obtained, there are several analyzes that must be performed before testing the VECM, namely the stationarity test, the optimal lag test, the cointegration test, the VECM estimate, and finally the impulse response function test. Based on the results of the analysis performed, the results show that for both long and short term exchange rate variables affect deposits, the inflation variable in this investigation period does not affect deposits and the IPI variable has a long term relationship with deposits, while in the short term has no relationship with third party funds. This article contributes to the effect of both long and short term macroeconomic variables on the interest of customers in depositing money with Islamic banks to be used as third party funds with Islamic banks.